Engaging underrepresented populations in public health monitoring: strategies for people with mild intellectual disability or low literacy skills - Meike C.M. Theunissen; Monique C.J. Koks-Leensen; Jane van Geenen; Geraline L. Leusink; Jenneken Naaldenberg; Kirsten E. Bevelander (International Journal for Equity in Health)
Abstract Background Recruitment challenges, the use of complex language, and reluctance toward research are factors that make people with low literacy skills (LL skills), such as people with mild intellectual disability (MID), an underrepresented group in public health monitoring questionnaires. As a result, little is known about the health status and needs of people with MID and/or LL skills, despite their higher health risks and greater support needs, reinforcing health inequalities. Therefore, this case study evaluates the development and implementation of an accessible online COVID-19 health monitoring survey (CHM) to gain insights into what is needed to engage these subpopulations in public health monitoring and promote equitable participation. Methods The CHM project was systematically analyzed using 319 documents related to the CHM development and implementation process. A semi-structured coding approach was used to identify strategies used to reach the target groups and elements influencing accessibility of the monitoring survey. Results Three key strategies to reach people with MID and/or LL skills were identified: stakeholder involvement, emphasizing the benefits of participation, and reducing barriers and reluctance to participate. Additionally, the inclusive development process played an essential role in improving accessibility and led to content, cognitive, and usability adjustments. Conclusions Our study illustrates that engaging people with MID and/or LL skills in public health monitoring relies on committed stakeholders who facilitate access to these groups and the involvement of experts by experience and co-researchers to align the monitoring survey with their experiences and abilities. These tailored methods and innovative recruitment strategies offer an opportunity for accessible and representative public health monitoring. Sustaining such monitoring approach could inform health policies that better reflect the needs of underrepresented groups and promote health equity.